Affective Influences on Energy-Related Decisions and Behaviors - Brosch, Tobias; Patel, Martin K.; Sander, David (Frontiers in Energy Research, 2014)
A successful energy transition will depend not only on the development of new energy technologies, but also on changes in the patterns of individual energy-related decisions and behaviors resulting in substantial reductions in energy demand. Across scientific disciplines, most theoretical approaches that try to understand energy-related decisions and behaviors focus mainly on cognitive processes, such as computations of utility (typically economic), the impact of cognitive heuristics, or the role of individual beliefs. While these models already explain important aspects of human decisions and behavior in the energy domain, we argue that an additional consideration of the contributions of emotional processes may be very fruitful for a deeper understanding of the issue. In this contribution, we outline a theoretical perspective on energy-related decisions and behaviors that integrates emotions, elicited by a cognitive-affective appraisal of the relevance of a situation, into a response system driving adaptive decisions and behaviors. We empirically investigate the explanatory power of the model variables to predict intentions to reduce energy use, demonstrating that the appraisal-emotion variables are able to account for additional variance that is not explained by two established models focused on cognitive processes (Theory of Planned Behavior and Value-Belief-Norm Theory). Finally, we discuss how the appraisal-emotion approach may be fruitfully integrated with other existing approaches and outline some questions for future research.